Development and performance evaluation of a low-cost custom-made vertical injection molding machine - Azuddin, M.; Choudhury, I.A.; Taha, Z. (Springer Verlag (Germany), 2015)
In this study, a concept of low cost injection molding system is presented. A prototype of a vertical injection molding machine has been designed and built based on the basic principles of injection molding. The developed system consists of plunger, melting chamber and custom-made mold. The plunger is used to deliver plastic melt from the melting chamber into the specific shape of the mold cavity. The performance of the custom-made machine is tested by successfully fabricated tensile specimen, Izod specimen, microchannels and gear shapes. The machine is capable of producing plastic parts of various shapes and sizes.